Micro-Raman and electronic structure study on kinetics of electronic excitations induced monoclinic-to-tetragonal phase transition in zirconium oxide films. Issue 106 (1st November 2016) - Rawat, Mukesh; Das, Arkaprava; Shukla, D. K.; Rajput, Parasmani; Chettah, A.; Phase, D. M.; Ramola, R. C.; Singh, Fouran
Abstract : Monoclinic-to-tetragonal phase transformation (PT) in sputtering grown zirconium oxide (ZrO2 ) films on silicon substrates by electronic excitation (EE) induced by swift heavy ion (SHI) irradiation is reported. Abstract : Monoclinic-to-tetragonal phase transformation (PT) in sputtering grown zirconium oxide (ZrO2 ) films on silicon substrates by electronic excitation (EE) induced by swift heavy ion (SHI) irradiation is reported. The density of EEs and the fluences of irradiation were varied for the better insight of phase transformation kinetics. The phase transition is well evident from the investigations using grazing incidence X-ray diffraction (GIXRD) and micro-Raman spectroscopy (mRS). Studies reveal a PT from the monoclinic to tetragonal phase. It is noted that at high fluence of Ag ion irradiation partly PT to cubic phase is also observed. However, it is clear from this study that this PT is not only due to transient temperature induced by SHI, but also attributed to the strain in the lattice created under the influence of the induced density of defects in the lattice. Interestingly, it may be noted that strain is well evident by the stiffening of the characteristic Raman modes of monoclinic phase. The modifications in electronic and local structure revealed using soft X-ray absorption spectroscopy (XAS) and X-ray absorption fine structure (XAFS) and found after fitting of Zr K-edge XAFS that phase transformation from m-ZrO2 to t-ZrO2 and/or c-ZrO2 upon Ni and Ag irradiation. Studies would elucidate a deeper understanding about the kinetics of PT under such non-equilibrium conditions.